Comparison of calcium metabolism in different subgroups of nephrotic syndrome in children - Mehta, Poonam; Nanda, Sanjiv (Indian Journal of Child Health, 2016)
Background: Children with nephrotic syndrome are at risk of altered calcium metabolism because of the disease per se as well as steroid therapy even before fall in glomerular filtration rate (GFR). Objective: To compare the pattern of alteration in calcium metabolism in different subgroups (infrequent relapser [IFR], frequent relapser or steroid-dependent nephrotic syndrome [FR/ SDNS], and patients in remission) of nephrotic syndrome in children. Methods: We conducted a cross-sectional study in the Department of Pediatrics, PGIMS, Rohtak. Children between 1 and 8 years of age were divided into three groups, viz., IFR (Group I), FR/SDNS (Group II), and patients in remission (Group III). Serum total calcium, ionized calcium, phosphate, parathormone (PTH), albumin levels, and urinary calcium and phosphate were measured, and X-rays of both lower limbs were done. Results: 10 patients in each group were compared. Serum total calcium, ionic calcium, and urinary calcium levels were decreased in patient with nephrotic syndrome during active disease. No difference was noted in serum phosphate, urinary phosphate, and GFR in all the three groups (p>0.05). Serum calcium and urinary calcium were significantly lower in Group II as compared to Group I (p